The evolution of large-bodied theropod dinosaurs during the Mesozoic in Asia - Brusatte, S. L.; Benson, R. B. J.; Xu, X. (Journal of Iberian Geology, 2010)
The fossil record of large-bodied, apex carnivorous theropod dinosaurs in Eastern Asia is now among the best understood in the world, thanks to new discoveries and reinterpretations of long-neglected fossils. Asia boasts the most complete record of Middle Jurassic theropods globally, as well as one of the best-studied Late Cretaceous theropod faunas, and new research is helping to fill what was previously a 60-million-year gap in the Early-mid Cretaceous fossil record of large Asian predators. In general, the bio-geographic affinities of large-bodied Asian theropods over time were intimately related to physical geography, and progressively more derived theropod clades evolved large body size and occupied the apex predator niche throughout the Jurassic and Cretaceous. During the Middle Jurassic, largely endemic clades of basal tetanurans were prevalent in Asia, whereas during the Late Jurassic mid Cretaceous more derived “intermediate” tetanuran theropods with cosmopolitan affinities occupied the large predator role, including sinraptorids, spinosauris, and carcharodontosaurians. Finalli, during the final 20 million years of the Cretaceous, more derived, bird-like coelurosaurs attained large body size. Foremost among these were the tyrannosaurids, a radiation of northern (Asian and North American) megapredators whose ascent into the apex predator niche was a delayed event restricted to the Campanian-Masastrichian. As Asia is the focus of intense ongoing dinosaur fieldwork, our undestarnding of large-bodied theropod evolution will continue to be refined with future discoveries.